Development of Fish Immunity and the Role of β-Glucan in Immune Responses - Rodrigues, Marianna V. [UNESP]; Zanuzzo, Fábio S; Koch, João Fernando A; de Oliveira, Carlos Alberto F; Sima, Petr; Vetvicka, Vaclav (MDPI, 2020)
Administration of β-glucans through various routes, including immersion, dietary inclusion, or injection, have been found to stimulate various facets of immune responses, such as resistance to infections and resistance to environmental stress. β-Glucans used as an immunomodulatory food supplement have been found beneficial in eliciting immunity in commercial aquaculture. Despite extensive research involving more than 3000 published studies, knowledge of the receptors involved in recognition of β-glucans, their downstream signaling, and overall mechanisms of action is still lacking. The aim of this review is to summarize and discuss what is currently known about of the use of β-glucans in fish.
Keywords: feeding; fish; glucan; health; immunity; infection